Child maltreatment among deaf and hard-of-hearing adolescent students: associations with depression and anxiety - Hammad, Mohammad Ahmed; Al-Otaibi, Mansour Nayef; Awed, Huda Shaaban (Frontiers in Psychology, 2024)
Objective: Child abuse and neglect have several short-and long-term consequences for the victim. Though Deaf and Hard-of-Hearing children are at higher risk of being maltreated as compared to hearing children, little research in Saudi Arabia has focused on this population. To determine the prevalence of child maltreatment and to examine its association with depression and anxiety among a sample of Deaf and Hard-of-Hearing students in Saudi Arabia, recruited from secondary schools in southern Saudi Arabia. Methods: The sample included 186 Deaf and Hard-of-Hearing students aged 14-17 years (M = 15.7 years; SD = 3.41 years). Data were collected using the Child Abuse Self-Report Scale, Center for Epidemiological Studies Depression Scale for Children, and Generalized Anxiety Disorder Questionnaire. Bivariate and Linear regression analyses were conducted using SPSS 20. Results: About 47.3% of the students were exposed severe to very severe child maltreatment. The severity of maltreatment varied based on parents' educational and income level, number of children in the family, the Deaf and Hard-of-Hearing student's gender, and parents' hearing status. Linear regression analysis indicated that child maltreatment was a significant predictor of depression and anxiety in this sample.Considering the socio-demographic factors influencing the prevalence of maltreatment in the present study, it seems important to work with parents of Deaf and Hard-of-Hearing children to improve their skills in rearing a child with special needs. Addressing the social stigma and social barriers experienced by DHH individuals through familial, institutional, and community interventions may be a first step towards long-term prevention of maltreatment among DHH children.